Interactions Between Exogenous Deoxyribonucleic Acid and Membrane Vesicles Isolated from Bacillus subtilis 168 - Joenje, H. (1974)
Membrane vesicles isolated from competent cultures of Bacillus subtilis 168 bound up to 20 μg of double-stranded deoxyribonucleic acid (DNA) per mg of membrane protein in the presence of ethylenediaminetetraacetate. The formation of the DNA-membrane complex was time, temperature, and pH dependent. Eighty per cent of the DNA could be removed from the complex by treatment with deoxyribonuclease I. Nevertheless, the DNA that remained attached to the vesicles appeared to have been attacked by the enzyme, suggesting that all the complexed DNA is located at the outer surface of the vesicles. Pretreatment of DNA with deoxyribonuclease I destroyed its affinity for the vesicles. The extent of binding decreased by the addition of Mg(2+) ions, especially at high DNA concentrations (more than 2 μg/ml). This effect was partially due to membrane-associated Mg(2+)-dependent endonucleolytic activity, which caused double-strand breaks in addition to single-strand nicks, and to exonuclease activity. The endonucleolytic activity was enhanced by heating the membranes at 80 C. DNA-membrane association was not markedly affected by sulfhydryl reagents, but was largely inhibited by formaldehyde. Endogenous competence-stimulating activity did not alter the DNA-binding capacity of the vesicles.